Rubinstein-Taybi 2 associated to novel EP300 mutations: deepening the clinical and genetic spectrum - María López; Alberto García-Oguiza; Judith Armstrong; Inmaculada García-Cobaleda; Sixto García-Miñaur; Fernando Santos-Simarro; Verónica Seidel; Elena Domínguez-Garrido (BMC, 2018)
Abstract Background Rubinstein-Taybi syndrome (RSTS) is a rare autosomal dominant neurodevelopmental disorder characterized by broad thumbs and halluces. RSTS is caused by mutations in CREBBP and in EP300 genes in 50-60% and 8%, respectively. Up to now, 76 RSTS-EP300 patients have been described. We present the clinical and molecular characterization of a cohort of RSTS patients carrying EP300 mutations. Methods Patients were selected from a cohort of 72 individuals suspected of RSTS after being negative in CREBBP study. MLPA and panel-based NGS EP300 were performed. Results Eight patients were found to carry EP300 mutations. Phenotypic characteristics included: intellectual disability (generally mild), postnatal growth retardation, infant feeding problems, psychomotor and language delay and typical facial dysmorphisms (microcephaly, downslanting palpebral fissures, columella below the alae nasi, and prominent nose). Broad thumbs and/or halluces were common, but angulated thumbs were only found in two patients. We identified across the gene novel mutations, including large deletion, frameshift mutations, nonsense, missense and splicing alterations, confirming de novo origin in all but one (the mother, possibly underdiagnosed, has short and broad thumbs and had learning difficulties). Conclusions The clinical evaluation of our patients corroborates that clinical features in EP300 are less marked than in CREBBP patients although it is difficult to establish a genotype-phenotype correlation although. It is remarkable that these findings are observed in a RSTS-diagnosed cohort; some patients harbouring EP300 mutations could present a different phenotype. Broadening the knowledge about EP300-RSTS phenotype may contribute to improve the management of patients and the counselling to the families.